Minor intron splicing is regulated by FUS and affected by ALS‐associated FUS mutants. (1st June 2016) - Reber, Stefan; Stettler, Jolanda; Filosa, Giuseppe; Colombo, Martino; Jutzi, Daniel; Lenzken, Silvia C; Schweingruber, Christoph; Bruggmann, Rémy; Bachi, Angela; Barabino, Silvia ML; Mühlemann, Oliver; Ruepp, Marc‐David
Abstract: Fused in sarcoma (FUS) is a ubiquitously expressed RNA‐binding protein proposed to function in various RNA metabolic pathways, including transcription regulation, pre‐mRNA splicing, RNA transport and microRNA processing. Mutations in the FUS gene were identified in patients with amyotrophic lateral sclerosis (ALS), but the pathomechanisms by which these mutations cause ALS are not known. Here, we show that FUS interacts with the minor spliceosome constituent U11 snRNP, binds preferentially to minor introns and directly regulates their removal. Furthermore, a FUS knockout in neuroblastoma cells strongly disturbs the splicing of minor intron‐containing mRNAs, among them mRNAs required for action potential transmission and for functional spinal motor units. Moreover, an ALS‐associated FUS mutant that forms cytoplasmic aggregates inhibits splicing of minor introns by trapping U11 and U12 snRNAs in these aggregates. Collectively, our findings suggest a possible pathomechanism for ALS in which mutated FUS inhibits correct splicing of minor introns in mRNAs encoding proteins required for motor neuron survival. Synopsis: Mutations in RNA‐binding protein FUS are frequently found in familial amyotrophic lateral sclerosis (ALS). This study shows FUS to control minor intron splicing via binding to the U11/12 snRNP and identifies target mRNAs that may contribute to disease pathology. Fused in sarcoma (FUS) interacts with the minor spliceosome and affects minor intron splicing. Loss of FUS results in a strong deregulation of minor intron‐containing genes. FUS with an ALS‐associated mutation mislocalizes to the cytoplasm and inhibits minor intron splicing. ALS‐associated cytoplasmic FUS sequesters U11 and U12 snRNA in cytoplasmic aggregates. Abstract : The RNA‐binding protein FUS, frequently mutated in amyotrophic lateral sclerosis (ALS), binds to U11 snRNP and affects splicing of minor intron‐containing mRNAs that may contribute to ALS pathology.